Digitale Datenbanken : Eine Medientheorie im Zeitalter von Big Data - Burkhardt, Marcus (2015)
We have long moved on from a mere information age to the era of big data. Here, databases represent both the enormous potential for gaining knowledge of data collection and the alarming information excesses of digital culture. Furthermore, the term refers to concrete technologies and processes of gathering and accessing digital information. Media theory has to locate databases in between these very different conceptions. Marcus Burkhardt retraces the history of databases and asks how technical procedures of processing digital information determine what can be found how in databases and what knowledge can be gained through them.